Massively parallel implementation of 3D‐RISM calculation with volumetric 3D‐FFT. Issue 18 (28th April 2014) - Maruyama, Yutaka; Yoshida, Norio; Tadano, Hiroto; Takahashi, Daisuke; Sato, Mitsuhisa; Hirata, Fumio
<x xml:space="preserve">Abstract</x> A new three‐dimensional reference interaction site model (3D‐RISM) program for massively parallel machines combined with the volumetric 3D fast Fourier transform (3D‐FFT) was developed, and tested on the RIKEN K supercomputer. The ordinary parallel 3D‐RISM program has a limitation on the number of parallelizations because of the limitations of the slab‐type 3D‐FFT. The volumetric 3D‐FFT relieves this limitation drastically. We tested the 3D‐RISM calculation on the large and fine calculation cell (20483 grid points) on 16, 384 nodes, each having eight CPU cores. The new 3D‐RISM program achieved excellent scalability to the parallelization, running on the RIKEN K supercomputer. As a benchmark application, we employed the program, combined with molecular dynamics simulation, to analyze the oligomerization process of chymotrypsin Inhibitor 2 mutant. The results demonstrate that the massive parallel 3D‐RISM program is effective to analyze the hydration properties of the large biomolecular systems. © 2014 Wiley Periodicals, Inc.